2017
DOI: 10.3892/ijmm.2017.3080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of isolation methods of exosomes and exosomal RNA from cell culture medium and serum

Abstract: Exosomes are cell-derived vesicles and are abundant in biological fluids; they contain RNA molecules which may serve as potential diagnostic biomarkers in 'precision medicine'. To promote the clinical application of exosomal RNA (exoRNA), many isolation methods must be compared and validated. Exosomes in cell culture medium (CCM) and serum may be isolated using ultracentrifugation (UC), ExoQuick or Total Exosome Isolation Reagent (TEI), and exoRNA may be extracted using TRIzol-LS, SeraMir, Total Exosome RNA Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
273
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(294 citation statements)
references
References 27 publications
20
273
0
1
Order By: Relevance
“…Several previous publications reported the feasibility and utility of sequencing small RNA in EVs isolated from serum, plasma, urine, and cell culture supernatant [2,2730]. Small RNA-Seq experiments often focus on valuable applications such as liquid biopsy-based diagnostics and, consequently, clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous publications reported the feasibility and utility of sequencing small RNA in EVs isolated from serum, plasma, urine, and cell culture supernatant [2,2730]. Small RNA-Seq experiments often focus on valuable applications such as liquid biopsy-based diagnostics and, consequently, clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…The conditioned medium was ultra‐centrifuged at 100,000 g for 70 minutes at 4°C as described previously . The exosomes pellets were resuspended in PBS and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Airway EVs from BALF of mice were isolated using the ExoQuick Exosome Precipitation Solution. Compared to the usual technique of ultracentrifugation, this provides a higher extraction efficiency but has the risk of protein contamination when used to isolate exosomes in cell culture media . The results showed that the amount of EVs observed increased by 8.9‐fold in the BALF of HDM‐exposed mice compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the usual technique of ultracentrifugation, this provides a higher extraction efficiency but has the risk of protein contamination when used to isolate exosomes in cell culture media. 82 The results showed that the amount of EVs observed increased by…”
Section: Gon Et Al 81 Analysed Variations In the Production Of Airwaymentioning
confidence: 97%